Electrical and Optical Characterization of Dielectric Barrier Discharge Produced in Atmospheric Air - Tyata, RB; Subedi, DP; Joshi, UM; Madhup, DK (Kathmandu University Journal of Science Engineering and Technology, 2009)
his paper reports the results concerning the production of Dielectric Barrier Discharge (DBD) at atmospheric pressure air and its electrical and optical characterization. The discharge was produced by applying high voltage AC source of frequency (10-30) kHz and potential difference of (0-20) kV across the electrodes. The discharge was characterized by measuring current and voltage with a high frequency digital oscilloscope. The optical characterization was made by taking the spectrums of discharge by optical emission spectrometer. The optical spectra in the range of 200 nm to 450 nm have been analyzed in order to estimate the electron temperature by intensity ratio method. Results showed that the electron temperature is about 1.9 eV.